2013
DOI: 10.1088/0022-3727/46/13/135004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of rapidly quenched rhombohedral Zr2Co11-based nanocomposites

Abstract: The effect of quench rate and Zr content on nanostructure and magnetic properties of melt-spun ZrxCo100−x (x = 16-21) is investigated. High quench rate favors the formation of rhombohedral Zr2Co11, which is the hard phase. The coercivity increases with an increase in quench rate. Zr addition in limited amounts decreases the grain size of magnetic phases, which may promote the effective exchange coupling of soft magnetic phases. Therefore, coercivity and maximum energy product of Zr2Co11-based materials are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 11 publications
(13 reference statements)
5
37
0
Order By: Relevance
“…Bulk Zr2Co11 alloys crystallize in rhombohedral or orthorhombic structures, [7,8] but the XRD pattern of Zr2Co11 nanoparticles (red curve) is in good agreement with that of the rhombohedral bulk structure (blue curve) as shown in figure 2a. Note that the Co-Zr bulk phase diagram, shown in figure 2b, indicates the formation of Zr2Co11 equilibrium phase only at a single composition (solid red vertical line).…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Bulk Zr2Co11 alloys crystallize in rhombohedral or orthorhombic structures, [7,8] but the XRD pattern of Zr2Co11 nanoparticles (red curve) is in good agreement with that of the rhombohedral bulk structure (blue curve) as shown in figure 2a. Note that the Co-Zr bulk phase diagram, shown in figure 2b, indicates the formation of Zr2Co11 equilibrium phase only at a single composition (solid red vertical line).…”
supporting
confidence: 65%
“…However, the range of alternative compounds with appreciable K1 and high Tc is limited, and the situation is often aggravated by their metastable nature and by the requirement of high-formation temperatures. [5][6][7][8][9][10][11][12] For example, two suitable candidates are Zr2Co11 and HfCo7, both crystallizing in noncubic structures, as necessary for high K1. However, the poor control over phase purity in traditionally prepared bulk alloys has an adverse effect on permanent magnetic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Depending on the preparation process, the crystal structure of Zr 2 Co 11 may be rhombohedral or orthorhombic. [4][5][6] Among these phases, rhombohedral Zr 2 Co 11 has been demonstrated to be the hard magnetic phase, 7 and a high quenching rate favors the formation of the hard magnetic phase. 8 Recently, an impressive energy product comparable to that of sintered SmCo 5 was obtained for the easy-axis aligned Zr 2 Co 11 -based nanocomposites produced by a single step cluster-deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a high quench rate is required in order to obtain good magnetic properties because it increases the volume fraction of the hard magnetic phase. [7] B addition was found to refine the grain size and increase the coercivity. [8] Ti addition suppressed the formation of Zr2Co11 dendrites upon solidification, refined the structure, and enhanced the coercivity.…”
Section: Introductionmentioning
confidence: 97%